Energy management platform for integrated battery‐based energy storage – solar PV system: a case study - Suthar, Sachinkumar; Pindoriya, Naran M. (Energy systems integration, 2020)
This study develops an energy management platform for battery‐based energy storage (BES) and solar photovoltaic (PV) generation connected at the low‐voltage distribution network. The sewage treatment plant of Gujarat International Finance Tec‐City located in the Gujarat state is considered as a testbed. The contribution of this case study is twofold: (i) Formulation and lab‐scale implementation of an optimal scheduling algorithm to charge/discharge BES while minimising the net energy purchase cost. (ii) Development of a fuzzy logic‐based speed control strategy for aeration blower to enhance the process efficiency. A stochastic optimisation problem was formulated as mixed‐integer linear programming to achieve the charging and discharging schedules of BES. The simulation study on speed control of aeration blower was carried out to demonstrate the air injection control for optimal dissolved oxygen level in the aeration basin at the testbed. Simulation results of the case study and lab‐scale hardware realisation (through real‐time digital simulator interfaced with modular hardware) were presented to validate the demand‐ and supply‐side energy management platform.